2015
DOI: 10.5958/2230-732x.2015.00048.0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Size of Fish Pond for Socio-Economical Development of Cachar (Assam)

Abstract: Aquaculture is one of the main sources of livelihood of the state of Assam in the northeast of India. In this study, Cachar district of Assam has been selected to study and assess the impact of various sizes of fish farm on the economic condition of farmers. The study was conducted in the villages of 5 blocks namely Borjalenga, Tapang, Narsingpur, Sonai and Palonghat with an objective to suggest optimum size of the pond and analyze the production rate of different type of fish farm. The data was collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is not surprising that the use of commercial feed is associated with higher production, yield, pro t, and productivity (pro t per square meter), as this pattern is consistent with other studies (Obwanga et al, 2020). Studies from Bangladesh and elsewhere have shown that high-quality feed is a key factor that drives productivity in sh farming (Aktar et al, 2018;Aung et al, 2021;Ragasa, Osei-Mensah, et al, 2022;Sarkar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that the use of commercial feed is associated with higher production, yield, pro t, and productivity (pro t per square meter), as this pattern is consistent with other studies (Obwanga et al, 2020). Studies from Bangladesh and elsewhere have shown that high-quality feed is a key factor that drives productivity in sh farming (Aktar et al, 2018;Aung et al, 2021;Ragasa, Osei-Mensah, et al, 2022;Sarkar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Small patches of mangroves are important to its value as an ecosystem for blue carbon stock but also to surrounding habitats as nodes for interconnectedness (Barbier 2017;Curnick et al 2019). In most developing regions, family-run aquacultural ponds were dominated, such as in India (Sarkar et al 2015) where 83% ponds had a size less than 0.3 ha, relatively similar to the fully-lost mangrove patches, 0.105 ha of average and 0.069 ha of median according to the GMW databases (Table 3). On the other hand, the abandoned aquacultural ponds were highly recommended as an effective measure to restore mangrove ecosystems recently (Stevenson et al 1999;van Bijsterveldt et al 2020).…”
Section: Impacts Of Global Mangrove Cover Changes Over the Periodsmentioning
confidence: 99%
“…Fishes are invariable living components of water bodies. These organisms are important food resources and good indicators of the ecological health of the water they inhabit (Sarkar et al 2015). Frei and Becker (2005b) reported irrigated rice areas with appropriate infrastructure can potentially be used for concurrent fish production.…”
mentioning
confidence: 99%